2006
DOI: 10.1103/physrevlett.97.140406
|View full text |Cite
|
Sign up to set email alerts
|

Bipartite Bell Inequalities for Hyperentangled States

Abstract: We show that bipartite Bell inequalities based on the Einstein-Podolsky-Rosen criterion for elements of reality and derived from the properties of some hyperentangled states allow feasible experimental verifications of the fact that quantum nonlocality grows exponentially with the size of the subsystems, and Bell loophole-free tests with currently available photodetection efficiencies.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
13
0

Year Published

2007
2007
2011
2011

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 30 publications
0
13
0
Order By: Relevance
“…Mermin showed that quantum mechanics violates Bell's equality by an amount that increases exponentially with the complexity of the system [71]. This violation was demonstrated using hyperentangled photon states [72,73].…”
Section: Orbital Angular Momentum Entanglementmentioning
confidence: 96%
“…Mermin showed that quantum mechanics violates Bell's equality by an amount that increases exponentially with the complexity of the system [71]. This violation was demonstrated using hyperentangled photon states [72,73].…”
Section: Orbital Angular Momentum Entanglementmentioning
confidence: 96%
“…The cat states demonstrated here, together with other graph states technically feasible within our experimental method (see Supplementary Fig. S1), create a versatile testing ground for the study of non-locality 28 , multipartite entanglement and many quantum information protocols. Indeed, by taking advantage of the hyper-entanglement, it is now possible to reach some experimental regimes that were hardly accessible before, for instance, demonstrations of the robustness of anyonic braiding 29 and topological cluster-state encoding 30 that require manipulation of 7-10 qubits.…”
Section: H H H H H H H H Hmentioning
confidence: 98%
“…The hyper-entangled states have been used to test "All-Versus-Nothing" (AVN) quantum nonlocality [11,12,15], and are shown to lead to an enhancing violation of local realism [16,17]. The states also enable to perform complete deterministic Bell state analysis [18] as demonstrated in [14,19].…”
mentioning
confidence: 99%